INFORMATION-ANALYTICAL SYSTEM OF MONITORING OF THE SHADOW OF NON-CASH FLOW: BASIC ELEMENTS, AUTHOR’S SIMULATION ALGORITHM - E. Baturina (Вестник университета, 2019)
The purpose of this article is to present the economic and mathematical toolkit for the analysis of information about the shadow activity of subjects of economic crimes and visualization of the structure of the information and analytical system for monitoring the shadow cash flow. The article presents a methodological review of the main provisions of the legal framework and scientific literature in the field of counteraction to legalization (laundering) of criminal proceeds and financing of terrorism. The characteristic of initial data has been given and the algorithm of their analysis has been described. The sequence of actions of users of the developed monitoring system has been revealed, which allows to calculate the minimum value of the shadow cashless cash flow, as well as quantitatively and qualitatively characterize the shadow economy, which is prospective in solving the problems of economic security of Russia.